Propagation of Stevia rebaudiana from stem cuttings - de Carvalho, Maria Angela Machado; Zaidan, Lilian B. P. (Pesquisa Agropecuaria Brasileira, 1995)
Rooting capacity of stem cuttings of S. rebaudiana was measured monthly during an one-year period. Highest percentages of live cuttings were found between May and October while rooting occurred preferentially from May to July, when new branches were used as cuttings. During the reproductive phase of the matrix plants rooting percentage was low. IBA promoted rooting and increased root number in August and September, whereas IAA and NAA were effective only in August. These substances had no effect on the survival of cuttings. Commercially available rooting products containing auxin-like substances were inefficient in inducing roots. Analysis of total soluble sugars (stevioside here included) present in leaves of plants obtained either from germination or stem cuttings pre-treated with root promoting substances showed no significant variation in relation to the origin of plants.